Polymorphism in transmembrane region of MICA gene and cholelithiasis - Shih, Shou-Chuan (World J Gastroenterol, 2003)
AIM: To study the significance of polymorphism of MHC class I chain-related gene A (MICA) gene in patients with cholelithiasis. METHODS: Subjects included 170 unrelated adults (83 males) with cholelithiasis and 245 randomly selected unrelated adults (130 males) as controls. DNA was extracted from peripheral leukocytes and analyzed for polymorphism of 5 alleles (A4, A5, A5.1, A6 and A9) of the MICA gene. RESULTS: There was no significant difference in phenotype, allele, and genotype frequencies of any of the 5 alleles between cholelithiasis patients and controls. CONCLUSION: This study demonstrates that MICA alleles studied bear no relation to cholelithiasis.